Sinonasal schwannoma in a patient with Eisenmenger syndrome - Reza Aditya Digambiro; Ashri Yudhistira; David Tjahyadi; Dewi Hastuty (PERHATI-KL, 2026)
Background: Sinonasal schwannoma is a rare tumor of the nasal cavity and paranasal sinuses, often presenting with recurrent epistaxis and nasal obstruction. Eisenmenger syndrome is a life-threatening cardiopulmonary condition resulting from uncorrected congenital heart disease. Purpose: To report a rare case of sinonasal schwannoma in a patient with Eisenmenger syndrome, and to explore therapeutic considerations. Case report: A 23-year-old male presented with recurrent nasal bleeding and progressive dyspnea. Imaging revealed a lobulated mass in the right nasal cavity. Histopathological evaluation confirmed sinonasal schwannoma. The patient also had an unrepaired secundum atrial septal defect with Eisenmenger physiology, rendering surgical excision high-risk. Clinical question: In patients with sinonasal schwannoma and Eisenmenger syndrome, when is surgical excision appropriate? Can conservative therapy provide adequate control in high-risk cases? Method: A literature search was conducted on PubMed, Medline, and Google Scholar using relevant keywords. Articles were selected based on the last 10 years of publication and full-text availability. Result: No studies specifically addressed this dual pathology. However, available literature emphasized the need for individualized management, with surgery being curative in healthy patients, and conservative observation preferred in high-risk cardiac cases. Conclusion: While surgical excision remains the “In patients with sinonasal hemangiopericytoma (HPC), conservative management may be justified in patients with Eisenmenger syndrome due to the prohibitive cardiopulmonary risks.